THE ROLE OF LAND DEED MAKING OFFICIALS IN LEGAL SETTLEMENT OF COMPLETE SYSTEM LAND REGISTRATION CERTIFICATES THAT OVERLAP IN SALE AND PURCHASE TRANSACTIONS IN TABANAN REGENCY - Nyoman Mahayu (Warmadewa Press, 2024)
Registration of Complete Systematic Land (PTSL) is the process of registering land for the first time This Complete Systematic Land Registration is one of the government programs due to the large number of uncertified land However, Complete Systematic Land Registration still encounters many problems in the field such as overlapping certificates Overlapping certificates can hinder the process of transferring rights such as hindering the registration of the transfer of land rights carried out by a Land Deed Official (PPAT) This research uses theory of legal certainty, the theory of legal protection and the theory of usefulness with empirical legal research. The legal consequence if the certificate of sale and purchase object overlaps is that the certificate cannot be used as valid proof of ownership of a piece of land In the case discussed here, the certificate issued in recent years must be cancelled first by submitting a request for cancellation of the certificate, then the certificate issued earlier will be processed for division according to the area of each ownership certificate (SHM) of the cancelled PTSL and processed to be in the name of each party. The role of PPAT in resolving overlapping land ownership certificates is by calling the parties whose certificates overlap, asking for the chronological origin of the rights application so that a duplicate certificate can be issued, and conveying it to the local Land Office to provide a solution to the problem of overlapping certificates.